1989
DOI: 10.1037/0022-3514.57.4.681
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for terror management theory: I. The effects of mortality salience on reactions to those who violate or uphold cultural values.

Abstract: On the basis of terror management theory, it was hypothesized that when mortality is made salient, Ss would respond especially positively toward those who uphold cultural values and especially negatively toward those who violate cultural values. In Experiment I, judges recommended especially harsh bonds for a prostitute when mortality was made salient. Experiment 2 replicated this finding with student Ss and demonstrated that it occurs only among Ss with relatively negative attitudes toward prostitution. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
1,005
3
24

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,019 publications
(1,063 citation statements)
references
References 23 publications
31
1,005
3
24
Order By: Relevance
“…The three studies reported in this article demonstrate the theory's potential for adding to the understanding of interpersonal and intergroup relations. The present research, along with that reported by Rosenblatt et al (1989), provides support for some terror management hypotheses concerning interpersonal relations, and thereby suggests that it may be fruitful to explore the wide range of additional hypotheses that can be derived from the theory concerning both this and other traditional areas of social-psychological inquiry (see Solomon et al, 1989, for other recent efforts to do so). In addition, the current findings suggest that refinements of the theory are needed regarding personality and situational variables that may influence how mortality salience affects interpersonal judgments.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The three studies reported in this article demonstrate the theory's potential for adding to the understanding of interpersonal and intergroup relations. The present research, along with that reported by Rosenblatt et al (1989), provides support for some terror management hypotheses concerning interpersonal relations, and thereby suggests that it may be fruitful to explore the wide range of additional hypotheses that can be derived from the theory concerning both this and other traditional areas of social-psychological inquiry (see Solomon et al, 1989, for other recent efforts to do so). In addition, the current findings suggest that refinements of the theory are needed regarding personality and situational variables that may influence how mortality salience affects interpersonal judgments.…”
Section: Discussionmentioning
confidence: 87%
“…Initial evidence supporting this proposition has recently been obtained in a series of six studies by Rosenblatt, Greenberg, Solomon, Pyszczynski, and Lyon (1989). In five of these studies, mortality salience was manipulated by having subjects fill out a mortality questionnaire that asked them to describe what will happen to them as they physically die and what the thought of their own death arouses in them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Religion serves as a resource for coping with trauma in a wide variety of ways (e.g., Vickberg et al, 2001;Walsh, King, Jones, Tookman, & Blizard, 2002; for a review, see Pargament, 1997), and feeling that religious beliefs are supported may enhance its effectiveness in general. However, a more direct explanation is provided by theory and research on terror management theory (TMT; Pyszczynski et al, 2003;Rosenblatt, Greenberg, Solomon, & Pyszczynski, 1989). Especially in the wake of a terror-inducing event like 9/11, increased national acceptance of religiosity could act as a form of support for a religious cultural worldview, thereby enhancing well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Participants volunteered to take part in a study titled Psychological Experiments. They read short descriptions of the following five classic findings in psychology: primacy and recency effects in memory (improved memory for items positioned at the beginning or at the end of a list; Robinson & Brown, 1926), encoding specificity (improved memory when information available at encoding is also available at retrieval; Thomson & Tulving, 1970), in-group favoritism (a greater tendency to favor one's own group members after experiencing failure than after experiencing success; Tajfel, 1982), the effects of mortality salience on derogation of moral transgressions (predicted by terror management theory; Rosenblatt, Greenberg, Solomon, Pyszczynski, & Lyon, 1989), and excitation transfer (the transfer of autonomic arousal from one situation to another; Zillmann, 1971).…”
Section: Methodsmentioning
confidence: 99%